Impact of climate change on agricultural production; Issues, challenges, and opportunities in Asia - Habib-ur-Rahman, Muhammad; Ahmad, Ashfaq; Raza, Ahsan; Hasnain, Muhammad Usama; Alharby, Hesham F.; Alzahrani, Yahya M.; Bamagoos, Atif A.; Hakeem, Khalid Rehman; Ahmad, Saeed; Nasim, Wajid; Ali, Shafaqat; Mansour, Fatma; et al. (Frontiers in Plant Science, 2022)
Agricultural production is under threat due to climate change in food insecure regions, especially in Asian countries. Various climate-driven extremes i.e. drought, heat waves, erratic and intense rainfall patterns, storms, floods and emerging insect pests have adversely affected livelihood of farmers. Future climatic predictions showed a significant increase in temperature, and erratic rainfall with higher intensity whilevariability exists in climatic patterns for climate extremes prediction. For mid-century (2040-2069), it is projected that there would be a rise of 2.8°C in maximum temperature and a 2.2°C in minimum temperature in Pakistan. To respond to adverse effects of climate change scenarios, there is a need to optimize climate-smart and resilient agricultural practices .Therefore, a case study was carried out to quantify climate change effects on rice and wheat crops and to develop adaptation strategies for rice-wheat cropping system during mid-century (2040-2069) as these two crops have significant contributions to food production. For quantification of adverse impacts of climate change in farmer field, multidisciplinary approach consisted of five climate models (GCMs), two crop models (DSSAT and APSIM) and an economic model [Trade-off Analysis, Minimum Data Model Approach (TOAMD)] was used in this case study. DSSAT predicted that there would be a yield reduction of 15.2% in rice and 14.1% in wheat and APSIM showed that there would be a yield reduction of 17.2% in rice and 12% in wheat. Adaptation technology, by modification in crop management like sowing time and density, nitrogen and irrigation application have potential to enhance the overall productivity and profitability of rice-wheat cropping system under climate change scenarios. Moreover, this paper reviews current literature regarding adverse climate change impacts on agricultural productivity, associated main issues, challenges and opportunities for sustainable productivity of agriculture to make sure food security in Asia. Flowing opportunities like altering sowing time and planting density of crops, crop rotation with legumes, agro-forestry, mixed livestock system, climate resilient plant, livestock and fish breeds, farming of monogastric livestock, early warning system and decision support system, carbon sequestration, climate, water, energy, and soil smart technologies and promotion of biodiversity have potential to reduce negative effects of climate change